Hazard or hardship : crafting global norms on the right to refuse unsafe work - Hilgert, Jeffrey, 1974- (Ithaca : Cornell University Press, 2016)
Today, hazardous work kills 2.3 million people each year and injures millions more. Among the most compelling yet controversial forms of legal protection for workers is the right to refuse unsafe work. The rise of globalization, precarious work, neoliberal politics, attacks on unions, and the idea of individual employment rights have challenged the protection of occupational health and safety for workers worldwide. This book presents the protection of refusal rights as a moral and a human rights question.
Previously issued in print: 2013.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 24, 2016).
Keywords: Industrial safety -- Law and legislation; Employee rights; Labor laws and legislation; Law; Health & safety issues; Constitutional & administrative law: general; Employment & labour law: general